Interstanding 2 : 5th Annual exhibition of the SCCA, Estonia. - Asoyeva, Sofiya; Borcic, Barbara; Garcia, David; Garrin, Paul; Haskel, Lisa; Huhtamo, Erkki; Keskküla, Ando; Kluitenberg, Eric; Kluszczynski, Ryszard W.; Kulik, Oleg; Mihhailov, Dmitri; Pantic, Drazn; et al. (Tallinn : Soros Center for Contemporary Arts, 1999)
Garcia, David ; Garrin, Paul ; Kulik, Oleg ; Smits, Rasa Smite & Raitis ; Juurak, Anu ; Katchuk, Gleb ; Kracina, Damijan ; Mamsikov, Maksim ; Martinis, Dalibor ; Pedanik, Martin ; Remme, Rauno ; Rigvava, Gia ; Tralla, Mare ; Ivekovic, Sanja ; Toomik, Jaan ; Graps, Jan J. ; Kruus, Maria ; Li, Pier ; Viljus, Mart ; Siib, Liina ; Keskküla, Ando ; Ojaver, Jüri ; Vaikla, Urmo ; Vaikla, Tüüne-Kristin ; Paap, Kristi ; Rannik, Kaire ; Teeäär, Berit ; Tiitsaar, Ketli ; Kelomees, Raivo ; Johannson, Tiia ; Sarapin, Virve ; Kaljo, Kai ; Kruusamäe, Ilmar ; Toomik, Jaan
biografie
Interstanding 2 : 5th Annual exhibition of the SCCA, Estonia. The series of art events Interstanding 2 will take place October 7 - 19, 1997.
Engels & Ests
kunstcatalogus
Keywords: Oekraïne; Polen